Wisata Sungai Kalimas sebagai Salah Satu Wisata Berkelanjutan di Surabaya - Truli Nugroho; Alexander Mario Retto Djong; Diana Martalia; Andreas Aris Eko Mulyono; Kristian Faskahariyanto; Suryo Adinugroho (Jurnal Minfo Polgan, 2025)
The development of urban river tourism is a strategic approach to addressing environmental degradation and the loss of a city's historical identity. The Kalimas River in Surabaya has significant historical value, serving as a major transportation and trade route from pre-colonial to colonial times. This study aims to analyze the Kalimas River as a sustainable, history-based tourism destination by reviewing environmental, socio-cultural, and economic aspects. The study employed a descriptive qualitative approach, supported by a survey of 100 tourist respondents. Data collection techniques included field observations, in-depth interviews, questionnaires, and documentation studies. The results showed that 82% of respondents considered the Kalimas River to have a positive contribution to river environmental conservation, 79% considered it to have strong historical educational value, and 76% stated that the river's presence had a positive impact on the local economy through MSMEs and culinary centers. These findings confirm that the Kalimas River has the potential to become a model for sustainable, history-based urban river tourism in Indonesia. This research is expected to serve as a reference for developing river tourism policies in major cities.